Pengaruh Sosioekonomi terhadap Tingkat Kepatuhan Pengungkapan Laporan Keuangan di Pemerintahan Provinsi Sumatra Barat - Nela Hajrianti (Jurnal Ecogen, 2022)
The purpose of this study is to identify socio-economic factors on the level of compliance with financial statement disclosures in the West Sumatra Provincial Government. In particular, this study examines the effect of regional independence, Prosperity level, and region's size on the level of compliance with the disclosure of regional government financial statements. The unit of analysis in this study is the regional government of West Sumatra, totaling 19 cities/districts in 2018-2020. The results of this study indicate an influence of regional independence, level of welfare, and regional size on the compliance of regional financial statement disclosures in city/district governments in West Sumatra. These results indicate that the socioeconomic factors can be used as a benchmark for disclosure compliance with local government accounting practices.